Aerobic capacity and heart rate variability in athletes - Zupet, P.; Finderle, Z. (Archivos de medicina del deporte, 2008)
While resting, athletes have a lower heart rate (HR) than untrained persons, whereas researchers do not share the opinion concerning the connection between the aerobic capacity and the variables of the heart rate variability (HRV). The aim of this study was to asses the correlation between maximal aerobic capacity and HRV indices in young male athletes. The study used a cross-sectional comparison of 27 top-level athletes (aged 17.3 ± 0.8, range 16-18 years; body height 177.1 ± 7.3, range 164 to 190 cm). None of them took any drugs. The maximal oxygen consumption (VO2max) was measured during an incremental continuous test on a treadmill ergometer. The criteria for the achievement of VO2- max were the absence of a further increase in VO2 despite the increasing load, RQ > 1.1 or subjective exhaustion. Body weight was used for the calculation of relative VO2max (ml/min/kg). Prior to the load test, a 10-minute ECG recording was obtained while each individual was resting in the supine position. The standard deviation of the heart rate (SDNN) and the proportion of interval differences of successive NN intervals greater than 50 ms (pNN50) were assessed through time domain method and total power (TP) through frequency domain method of HRV analysis. VO2max measured from our athletes ranged from 48,7 ml/kgmin to 75,3 ml/ kgmin. We found a significant relationship between maximal aerobic capacity and a parameter which estimates high frequency variation in heart rate (pNN50: r=0,435, p=0,02). On the other hand, no significant relationship was found between VO2max and parameters which are infl uenced by high and low frequencies (SDNN, TP). In conclusion, our data indicated that enhanced aerobic capacity increases HR vagal control and provide further support for autonomic system playing a role in adaptation to training.